Case report: A novel de novo loss of function variant in the DNA-binding domain of TBX2 causes severe osteochondrodysplasia - Rafeeq, Misbahuddin M.; Murad, Hussam Aly Sayed; Najumuddin,; Ullah, Samee; Ahmed, Zaheer; Alam, Qamre; Bilal, Muhammad; Habib, Alaa Hamed; Sain, Ziaullah M.; Khan, Muhammad Jawad; Umair, Muhammad (Frontiers in Genetics, 2023)
Background: T-box family members are transcription factors characterized by highly conserved residues corresponding to the DNA binding domain known as the T-box. TBX2 has been implicated in several developmental processes, such as coordinating cell fate, patterning, and morphogenesis of a wide range of tissues and organs, including lungs, limbs, heart, kidneys, craniofacial structures, and mammary glands. Methods: In the present study, we have clinically and genetically characterized a proband showing a severe form of chondrodysplasia with developmental delay. Whole exome sequencing (WES), Sanger sequencing, and 3D protein modeling were performed in the present investigation. Results: WES revealed a novel nonsense variant (c.529A>T; p.Lys177*; NM_005994.4) in the TBX2. 3D-TBX2 protein modeling revealed a substantial reduction of the mutated protein, which might lead to LOF or NMD. Conclusion: This study has not only expanded the mutation spectrum in the gene TBX2; it might facilitate diagnosis and genetic counseling of related features in affected families.